Model Keluarga Bahagia Menurut Islam - Hj Jaapar, Nur Zahidah; Azahari, Raihanah (Jurnal Fiqh, 2011)
This article aims to elaborate upon the theory of Family Happiness based on the Islamic Model of Family Wellbeing. Reference is made to the views of Muslim philosophers to create an Islamic model of family wellbeing. This article concludes that happiness is dependent upon two factors faith and charity.